Alcance jurídico de la cooperación eficaz en los delitos contra la eficiencia de la administración pública - Andrade Martínez, Adolfo Antonio (2020)
The purpose of this research project is to demonstrate that effective cooperation leaves impunity for the crime of Public Administration Efficiency, so we propose that a legal scope be made, to formal requirements, especially when Public Officials are immersed, specifically in the crime of Peculate, since it is important to study the legal phenomenon of Effective Cooperation, especially since there is no procedure, nor proportionality at the time of granting the benefit, and this leads to crimes against the Efficiency of Public Administration, remain unpunished, in the eyes of society, for this we propose that the reform be carried out, Article 492, of the Organic Integral Criminal Code. The Premial Criminal Law has caused pressure in some countries and created aberrant laws that violate all the guarantees of any Civilized Criminal Law, where it has been created: Retroactive Criminal Laws, secret criminal proceedings, special commissions, limitations on Defense Law, Instructions to Judges, prizes to reporters, judicial authorizations to commit crimes, etc. They revive the old inquisitorial institutions in this way and are legitimized by their intended practicality…………